Criminological Organized Network Models of Human Smuggling: An Analysis with Special reference to the United Nations Convention on Transnational Organized Crime and the Protocol against Smuggling of Migrants - Y. Kathirgamathamby (The Open University of Sri Lanka, 2021)
The Criminological Organized Network Model (CON Model), one of the theoretical models propounded by several scholars, postulates that the assignment of human smuggling is carried out by wellorganized international criminal networks. This model elucidates the objectives, the form, and the tasks carried out by organized criminal groups. The United Nations Convention on Transnational Organized crime 2000 (UNCTOC) and the Protocol against Smuggling of Migrants via Air, Sea and Land (HS Protocol) are the major international legal instruments governing human smuggling. Both these instruments state that human smuggling is a transnational crime committed by organized criminal groups. Against this background the main objective of the paper is to examine as to how far the features of the CON Model has been translated into international legal instruments particularly in Article 2(a) of the UNCTOC and Article 3(a) of the HS protocol in order to identify the gaps in the said articles and make recommendations for comprehensive legal provisions in line with the CON Model of human smuggling. Doctrinal research incorporating conceptual, descriptive, interpretative, analytical, and comparative methodology have been utilized in the research. The paper discusses and analyzes the objectives, nature, and tasks of organized crime groups relevant to the definition of an organized criminal group and human smuggling as per the UNCTOC and the HS Protocol and draws out gaps in these definitions. It can be noted that the definition of the organized crime groups fails to be sufficiently comprehensive. There is uncertainty in the human smuggling protocol read with UNCTOC as to whether people who help the human smuggling operation on humanitarian grounds are guilty or not. The paper, it is hoped, will contribute to the establishing of a more comprehensive definition of an Organized Criminal Group (OCG) and set out a clear demarcation and differentiation between people who act with profit-making motives and the sympathetic supporters.